Zjazdy książąt i stanów Śląska w latach 1332–1335 - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In the study the author presents the results of his search for traces of collective political activity of Silesian dukes and estates in 1332–1335, which have been largely omitted from the existing literature on the subject. The author has managed to confirm or at least demonstrate the likelihood that congresses did take place every year in the period in question, with the exception of 1335. There were three types of congresses: of dukes, landed gentry from a given district (weichbild) and towns from a given principality. Worthy of note is the fact that the congresses were held mainly in Silesia proper, that is in Lower Silesia, as the region would later come to be called.
Keywords: zjazdy książąt; Śląsk; 14 w.